Transcriptome Analysis of Host Inflammatory Responses to the Ectoparasitic Mite Sarcoptes scabiei var. hominis - Shehwana, Huma; Ijaz, Sadaf; Fatima, Abeera; Walton, Shelley; Sheikh, Zafar Iqbal; Haider, Waseem; Naz, Shumaila (Frontiers in Immunology, 2021)
Scabies, a human skin infestation caused by the ectoparasitic mite Sarcoptes scabiei var. hominis, affects more than 200 million people globally. The prevailing knowledge of the disease process and host immune response mechanisms is limited. A better understanding of the host-parasite relationship is essential for the identification of novel vaccine and drug targets. Here we aimed to interrogate the transcriptomic profiles of mite infested human skin biopsies with clinical manifestations of ordinary scabies subjects (“OS”; n = 05) and subjects naive to scabies (“control”; n = 03) using RNASeq data analysis. A combined clustering, network and pathway mapping approach enabled us to identify key signaling events in the host immune and pro inflammatory responses to S. scabiei infestation. The clustering patterns showed various differentially expressed genes including inflammatory responses and innate immunity genes (DEFB4A, IL19, CXCL8, CSF3, SERPINB4, S100A7A, HRNR) and notably upregulation of the JAK-STAT pathway in scabies infested samples. Mite infested human skin biopsies (GSE178563) were compared with an ex-vivo porcine infested model (E-MTAB-6433) and human skin equivalents (GSE48459). Marked enrichment of immune response pathways (JAK-STAT signaling, IL-4 and IL-13 pathway and Toll receptor cascade), chemokine ligands and receptors (CCL17, CCL18, CCL3L1, CCL3L3, CCR7) and cytokines (IL13, IL20) were observed. Additionally, genes known for their role in psoriasis and atopic dermatitis were upregulated e.g., IL-19. The detailed transcriptomic profile has provided an insight into molecular functions, biological processes, and immunological responses and increased our understanding about transcriptomic regulation of scabies in human.